2021
DOI: 10.1080/1406099x.2021.1990473
|View full text |Cite
|
Sign up to set email alerts
|

Local business environment, managerial expertise and tax corruption of small- and medium-sized enterprises

Abstract: While tax corruption is widespread in many countries with inferior business environments, it is unclear how the characteristics of taxpayers influence their tax behaviour. This study investigates the impact of manager expertise on firms' tax corruption in a transition economy. Using a longitudinal dataset consisting of small-and medium-sized enterprises in Vietnam over the period from 2005 to 2015, we find that firms which are managed by more able managers are more likely to engage in tax corruption and are wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A survey of 147 countries found that the primary challenge in running a company is the difficulty that business people face in comprehending tax regulations (Bhalla et al, 2022). The complexity of tax regulations and disorganized tax administration costs, coupled with limited tax knowledge, can lead to companies not utilizing their tax-saving potential legally and optimally, thus hindering business performance growth (Vu et al, 2021).…”
Section: Relationship Between Tax Knowledge and Business Performancementioning
confidence: 99%
“…A survey of 147 countries found that the primary challenge in running a company is the difficulty that business people face in comprehending tax regulations (Bhalla et al, 2022). The complexity of tax regulations and disorganized tax administration costs, coupled with limited tax knowledge, can lead to companies not utilizing their tax-saving potential legally and optimally, thus hindering business performance growth (Vu et al, 2021).…”
Section: Relationship Between Tax Knowledge and Business Performancementioning
confidence: 99%
“…The owners who possess a variety of managerial expertise able to make the business perform well. Although knowledge is the key to a better future, knowledge is also associated with illegal activities committed in business such as bribery (Hoang Vu et al, 2021). In the study conducted among Vietnamese SMEs, they found managers that who are very expert in tax are prone to be involved in tax corruption and bribery.…”
Section: Managerial Expertise Such As Business Planning and Entrepren...mentioning
confidence: 99%
“…Nguyen and Wong (2021) used an extended model based on data from Vietnamese listed firms; according to the findings of the study, improvements in the business environment reduce firms' cash holdings and vice versa. Vu et al (2021) used a 10-year longitudinal dataset of Vietnamese SMES and found that improvements in the quality of the business environment contribute to less tax corruption in transition economies. Cui et al (2022) concluded that improving the business environment promotes the economic growth of trading partners.…”
Section: Business Environmentmentioning
confidence: 99%